Salinity change evokes stress and immune responses in Atlantic salmon with microalgae showing limited potential for dietary mitigation - van Muilekom, Doret R.; Mueller, Jonas; Lindemeyer, Jacqueline; Schultheiß, Thekla; Maser, Edmund; Seibel, Henrike; Rebl, Alexander; Schulz, Carsten; Goldammer, Tom (Frontiers in Physiology, 2024)
Smoltification was found to impact both immune and stress responses of farmed Atlantic salmon (Salmo salar), but little is known about how salinity change affects salmon months after completed smoltification. Here, we examined (1) the effect of salinity change from brackish water to seawater on the stress and immune responses in Atlantic salmon and (2) evaluated if functional diets enriched with microalgae can mitigate stress-and immune-related changes. Groups of Atlantic salmon were fed for eight weeks with different microalgae-enriched diets in brackish water and were then transferred into seawater. Samples of the head kidney, gill, liver and plasma were taken before seawater transfer (SWT), 20 hours after SWT, and 2 weeks after SWT for gene-expression analysis, plasma biochemistry and protein quantification. The salmon showed full osmoregulatory ability upon transfer to seawater reflected by high nkaα1b levels in the gill and tight plasma ion regulation. In the gill, one-third of 44 investigated genes were reduced at either 20 h or two weeks in seawater, including genes involved in cytokine signaling (il1b) and antiviral defense (isg15, rsad2, ifit5). In contrast, an acute response after 20 h in SW was apparent in the head kidney reflected by increased plasma stress indicators and induced expression of genes involved in acute-phase response (drtp1), antimicrobial defense (camp) and stress response (hspa5). However, after two weeks in seawater, the expression of antiviral genes (isg15, rsad2, znfx1) was reduced in the head kidney. Few genes in the gill were downregulated by a diet with 8% inclusion of Athrospira platensis. The results of the present study indicate that salinity change months after smoltification evokes molecular stress-and